2010
DOI: 10.1021/jp109215q
|View full text |Cite
|
Sign up to set email alerts
|

Tautomer Selective Photochemistry in 1-(Tetrazol-5-yl)ethanol

Abstract: A combined matrix isolation FTIR and theoretical DFT/B3LYP/6-311++G(d,p) study of the molecular structure and photochemistry of 1-(tetrazol-5-yl)ethanol [1-TE] was performed. The potential energy surface landscapes of the 1H and 2H tautomers of the compound were investigated and the theoretical results were used to help characterize the conformational mixture existing in equilibrium in the gas phase prior to deposition of the matrices, as well as the conformers trapped in the latter. In the gas phase, at room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…If the molecule exhibits tautomerism, tautomer-selective photochemistry may take place. [19][20][21] The structural features that render tetrazolyl ethers excellent substrates for transfer hydrogenolysis may also influence their photochemistry. Among 1,5-disubstituted tetrazoles, 5-aryloxy-1-phenyltetrazoles appear to be especially interesting, since the central oxygen links an aromatic and an electron-withdrawing heteroaromatic system.…”
Section: Introductionmentioning
confidence: 99%
“…If the molecule exhibits tautomerism, tautomer-selective photochemistry may take place. [19][20][21] The structural features that render tetrazolyl ethers excellent substrates for transfer hydrogenolysis may also influence their photochemistry. Among 1,5-disubstituted tetrazoles, 5-aryloxy-1-phenyltetrazoles appear to be especially interesting, since the central oxygen links an aromatic and an electron-withdrawing heteroaromatic system.…”
Section: Introductionmentioning
confidence: 99%
“…Tautomerism has been extensively studied in a great variety of azoles [5][6][7][8] as well as in other similar systems, including tetrazoles. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] In these studies, the preference for a specific a) Author to whom correspondence should be addressed. Electronic mail: reva@qui.uc.pt tautomer or tautomers at different proportions, according to the physical state of the compound, has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Ismail et al, 54 presented a very interesting study where tautomer selective photochemistry was observed for 1-(tetrazol-5-yl)ethanol . The potential energy surface landscapes of the 1H and 2H tautomers of the compound were investigated and the theoretical results were used to help characterize the conformational mixture existing in equilibrium in the gas phase prior to deposition of the matrices, as well as the conformers trapped in the latter.…”
Section: Fragmentation Reactions and Formation Of Complexes Or Weaklymentioning
confidence: 99%
“…18 Simplified scheme showing the observed photoprocesses resulting from UV irradiation (lW 200 nm) of matrix-isolated monomeric 1-(tetrazol-5-yl)ethanol. 54 tetrazole hydrogen to the oxygen atom of substituent. The ring-opening reaction then requires simultaneous cleavage of this bond (Fig.…”
Section: Fragmentation Reactions and Formation Of Complexes Or Weaklymentioning
confidence: 99%